Learning from Posyandu Cadres about Posyandu in Penggilingan Village, Cakung District - Novy Ernawaty; Memed Setiawan; Al-Bahra Al-Bahra (JOURNAL EDUCATIONAL OF NURSING(JEN), 2022)
Posyandu activities are prioritized on five programs including family planning (Family Planning), MCH (Maternal and Child Health), nutrition, immunization and diarrhea management. Posyandu should be in a place that is easily accessible by the community and determined by the community. Posyandu activities can be carried out at existing service posts, people's houses, village halls, RK/RT meeting places or in special places built by the community. This study aims to provide learning to posyandu cadres about posyandu in Penggilingan Village, Cakung District. This research is descriptive in nature. The cadre population is 36 posyandu cadres. The sample used a non-probability sampling technique, namely 36 posyandu cadres. Data collection using a questionnaire. Data analysis used descriptive analysis techniques, then univariate analysis used frequency and percentage distributions. The characteristics of respondents based on age found that the highest number of respondents were in the category of over 35 years of age with 28 people (77.8%), characteristics based on education the results showed that the highest number of respondents were in the category of junior high school graduates with 13 respondents (36.1%), and the characteristic category based on occupation, it was found that the highest number of respondents were in the category of working mothers (laborers, traders, and employees) as many as 22 respondents (61.1%). The level of knowledge of respondents about posyandu is in the category of good level of knowledge, namely as many as 26 respondents (72.2%).